Attitudes of Kurdish university students towards the English language, English language education policies, and English language learning purposes - Qadir, Sarkawt; Omar, Rukhsar (Humanities Journal of University of Zakho, 2023)
Similar to other parts of the world, Kurdish speakers of English have been subject to English fever. They have a strong desire to learn and speak English. An army of teachers is currently teaching Kurdish speakers to learn English. However, few of them acquire the required level of English when they move from high school level to university one. This might partly be associated with their attitudes towards not only the English language but the English language policies and practices that are currently adopted. Attitudes towards the English language have been extensively investigated both quantitatively and qualitatively in diversified educational and cultural contexts. Furthermore, a few studies have been conducted to investigate the attitudes of Kurdish students towards the English language, but their attitudes to English language education policies and English language learning purposes have yet remained unknown. Therefore, this study is anchored on investigating Kurdish undergraduate students’ attitudes towards the English language, English language education policies that are currently applied in Iraqi Kurdistan, and students’ purposes for learning English. It further concentrates on the effect of such variables as gender and year of study on attitudes. For this purpose, the study utilized a questionnaire consisting of 42 items on a 6-point Likert scale surveyed online on a sample of 154 students belonging to different ages, genders, years of study, and majors. The analysis of the data showed that Kurdish university students held neutral to mildly positive attitudes to the English language and English learning purposes. Nevertheless, they held slightly positive attitudes towards English language education policies. The study concludes that, although fundamental transformations have been achieved in the past two decades, the neutral attitudes show that efforts are yet to be made to satisfy students’ needs and desires, particularly with regard to the policies and practices that are currently adopted. This study, different from previous ones, reveals students’ attitudes towards English education policies whose findings are significant for English language education policymakers.